Literary Parody of Russian Communism Harmonizing to George Orwell’s Two Novels "Animal Farm" and "Nineteen Eighty Four" - Hazhar Ramadhan Ahmed; Shabanb; Mohammed, Othman (International Journal of Language and Literary Studies, 2021)
This Paper concerns within one of the foremost critical viewpoints in literature, where the metaphorical and mocking centrality of ‘Animal Farm’ and ‘Nineteen Eighty-Four’ by George Orwell is highlighted, Through ’Animal Farm’ and ’Nineteen Eighty-Four’ Orwell by implication assaults Russian communism, Orwell combines political reason with a creative one to voice his critical conviction. Orwell utilized parody to grant more impact and understanding of his two books. Parody in Literature constitutes one of the viable literary strategies writers utilize in their stories to assault an individual, a thought, or behaviour that they think awful or silly. An essayist in parody employments an anecdotal character, which stands for genuine individuals to uncover and condemn their debasement, the analyst takes after the descriptive-analytic strategy. Animal Farm is ostensibly an animal story, but deep down it is a moral story, a parody around the Russian Revolution of 1917 with wrong qualities of course battle. To a few degrees, Nineteen Eighty-Four moreover centres on the concepts of the free venture and person flexibility, which don’t really exist. There as it were remains a world of scorn. Segregation, and fear as superpowers. Eurasia and East Asia are two superpowers and Oceania, the third one, is continuously at war with one of them. By using political parody within the two books, the writer makes a consul and curiously air that influences progressing the plot in arrange to provide a clear understanding and improving its structure. In arrange to connect the investigate questions and the discoveries, a nitty-gritty clarification on the concept of the parody has been displayed as a curiously literary method; something else, peruses would not discover a relationship between the two works. At long last, Orwell actually succeeds in encoding his knead within the shape of a parody and hence peruses associated with him.